A Relational Framework for Integrating the Study of Empathy in Children and Adults. (October 2020) - Main, Alexandra; Kho, Carmen
The development of empathy is central to positive social adjustment. However, issues remain with integrating empathy research conducted with children, adolescents, and adults. The current article (a) provides an overview of how empathy is typically conceptualized and measured in child development and adult research, (b) describes outstanding issues concerning child development and adult research on empathy, and (c) outlines how a relational approach can provide clarity regarding how empathy develops over the course of development. We conclude by offering suggestions for future research on the development of empathy across the lifespan.